2016
DOI: 10.1111/nph.14330
|View full text |Cite
|
Sign up to set email alerts
|

The transition from somatic to germline identity shows conserved and specialized features during angiosperm evolution

Abstract: How and why specific plant cells adopt germline identity during ovule development has proved challenging to address, and the pathways that are active in the ovules of basal/early-divergent angiosperms possessing a multilayered nucellus are still unclear. Here, we compare megasporogenesis between two early-divergent angiosperms (Annona cherimola and Persea americana) and the evolutionarily derived Arabidopsis thaliana, studying the three-dimensional spatial position of the megaspore mother cell (MMC), the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 120 publications
(171 reference statements)
6
53
1
Order By: Relevance
“…A similar pattern was observed for DR5:nlsGFP in young ovules from the daisy Hieracium piloselloides (Figure D, E; Tucker et al ), in early divergent angiosperms (Lora et al ) and in maize (Forestan and Varotto ; Lituiev et al ). In maize, DR5rev::mRFPer shows abundant expression in antipodal cells at the chalazal pole of the female gametophyte (Chettoor and Evans ).…”
Section: Locating Auxin In the Reproductive Organs And Interactions Bsupporting
confidence: 78%
See 2 more Smart Citations
“…A similar pattern was observed for DR5:nlsGFP in young ovules from the daisy Hieracium piloselloides (Figure D, E; Tucker et al ), in early divergent angiosperms (Lora et al ) and in maize (Forestan and Varotto ; Lituiev et al ). In maize, DR5rev::mRFPer shows abundant expression in antipodal cells at the chalazal pole of the female gametophyte (Chettoor and Evans ).…”
Section: Locating Auxin In the Reproductive Organs And Interactions Bsupporting
confidence: 78%
“…Upon establishment of the primary germline cell (megaspore mother cell; MMC), expression of TAA1 is detected in the chalazal nucellus and inner integument primordia (Ceccato et al ; Robert et al ), which is complemented by expression of PIN1 and DR5 markers in the distal nucellar tissue (Pagnussat et al ; Bencivenga et al ). A similar pattern of PIN1 expression has been observed in cherimoya, avocado (Lora et al ) and maize (Forestan et al 2012). This pattern suggests that as ovule development proceeds, auxin is synthesized in the base and transported into the nucellar tissue surrounding the MMC, where it affects a response as the ovule progresses through meiosis and early (FG1 and FG2) stages of gametophyte development.…”
Section: Auxin Function During Female Germline Formation and Maturationsupporting
confidence: 76%
See 1 more Smart Citation
“…AGPs have also been observed in the micropylar nucellus of Amaranthus hypochondriacus (Coimbra & Salema, ) and in the micropyle and synergids of Arabidopsis thaliana (Coimbra et al ., ). Recent results have shown that cell wall polymers, including AGPs, mark the female germline in Annona cherimola , but not in Arabidopsis , and this could reflect the different microenvironment of nucellar cells around and during female germline development (Lora et al ., ). A different microenvironment is also found around the egg apparatus in the mature female gametophyte of Annona and Arabidopsis , and could also have implications for pollen tube guidance that have not yet been studied.…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, the capacity of these sugary chains to detach from the cell wall and be secreted to the apoplast (Majewska‐Sawka and Nothnagel, 2000; Ellis et al, 2010) makes AGPs excellent candidates for cell–cell communication, critical during pollen–pistil interactions. During the reproductive process, AGPs have been associated with female gametogenesis (Acosta‐García and Vielle‐Calzada, 2004; Coimbra et al, 2007; Lopes et al, 2016; Lora et al, 2017), somatic embryogenesis (Pennell et al, 1992; van Hengel et al, 2002), pollen tube guidance toward the ovules (Mizukami et al, 2016), and pollen grain recognition (Pereira et al, 2015). Additionally, the secretion of AGPs correlates with the temporal window in which interactions between pollen tubes and the carpel tissues occur (Losada and Herrero, 2012, 2014, 2017; Pereira et al, 2015; Mizukami et al, 2016).…”
mentioning
confidence: 99%